ChemInform Abstract: A General, Scalable, Organocatalytic Nitro‐Michael Addition to Enones: Enantioselective Access to All‐Carbon Quaternary Stereocenters. Issue 31 (August 2015) - Gu, Xiaodong; Dai, Yuanyuan; Guo, Tingting; Franchino, Allegra; Dixon, Darren J.; Ye, Jinxing
Abstract A tert‐leucine‐derived chiral diamine efficiently catalyzes the asymmetric Michael addition of nitromethane to five, six‐, and seven‐membered β‐substituted cyclic enones furnishing the corresponding adducts with quaternary stereocenter in excellent enantioselectivities.